Method of determining the location of the pinch point using seismic survey in some areas of the Absheron Peninsula - Ahmadov, T. R. (Revista de la Universidad del Zulia, 2019)
The article is devoted to determining the exact position of the point of pinching sediments by 2D and 3D seismic. It is noted that industrial oil and gas production has a nearly two-century history and the main developed fields are concentrated in anticlinal traps that have already exhausted their resources. At present, there is an intensive search for non-anticline hydrocarbon traps both in the Absheron Peninsula and beyond; most traps are associated with wedging out sediment complexes. It is emphasized that the study of seismic pinch-out zones in Azerbaijan does not meet difficulties, and the situation of studying determining the position of the pinch point is different. Three methods for determining and clarifying the position of the pinch point are proposed: a - using attribute analysis or instantaneous dynamic characteristics of the wave field; b - the method of determining the quality of the recording according to the Vertical Seismic Profiling (VSP); c - with spectral analysis of seismic records based on Fourier transform. All three methods were tested on different seismic and geological conditions, gave good results, and showed high geological efficiency.